Understanding the influence of perceived fatigue on coordination during endurance running. Issue 5 (2nd September 2020) - Bailey, Joshua P.; Dufek, Janet S.; Freedman Silvernail, Julia; Navalta, James; Mercer, John
ABSTRACT: During the course of a training programme, runners will typically increase running velocity and volume possibly encountering fatigue during a run, which is characterised as a feeling of general tiredness. The purpose of the current study was to identify whether or not level of perceived fatigue affects coordination and coordination variability in healthy runners during the recovery velocity of an endurance interval run. A total of 20 endurance runners completed a 1-hour run that included running velocity intervals at 75% of estimated 10 k race pace (5 minutes) and estimated 10 k race pace (1 minute). After each run, participants completed a fatigue questionnaire and were grouped based on their post-run self-reported perceived fatigue. 3D motion capture data were collected during the run and analysed to generate coordination patterns and variability of the patterns as dependent variables. Multiple mixed model ANOVAs were conducted to test for differences between perceived fatigue groups. Coordination and variability differences were reported in a number of couplings during transition phases (late and early stance) and events (toe-off and foot contact) of the gait cycle. It was concluded that the level of perceived fatigue affected coordination and coordination variability during the recovery velocity of a 1-hour interval run.